Map-Based Cloning and Characterization of Br-dyp1, a Gene Conferring Dark Yellow Petal Color Trait in Chinese Cabbage (Brassica rapa L. ssp. pekinensis) - Yang, Shuangjuan; Liu, Honglei; Zhao, Yanyan; Su, Henan; Wei, Xiaochun; Wang, Zhiyong; Zhao, Xiaobin; Zhang, Xiao-Wei; Yuan, Yuxiang (Frontiers in Plant Science, 2022)
Flower color is an important trait in Brassica species. However, genes responsible for the dark yellow flower trait in Chinese cabbage have not been reported. In this study, we identified a dark-yellow-flowered Chinese cabbage line SD369. Genetic analysis indicated that the dark yellow flower trait in SD369 was controlled by a single recessive locus, Br-dyp1 (dark yellow petal color 1 in Brassica rapa). Using bulked segregant RNA sequencing (BSR-Seq) and kompetitive allele specific PCR (KASP) assays, Br-dyp1 was fine-mapped to an interval of 53.6 kb on chromosome A09. Functional annotation analysis, expression analysis and sequence variation analysis revealed that Bra037130 (BraA09.ZEP), which encodes a zeaxanthin epoxidase, was the most likely candidate gene for Br-dyp1. Carotenoid profile analysis suggested that Bra037130 (BraA09.ZEP) might participate in the epoxidation from zeaxanthin to violaxanthin. The 679 bp insertion in dark yellow petal caused premature stop codon, thus caused the loss-of-function of the enzyme ZEP, which disturbed the carotenoid metabolism, and caused the increased accumulation of total carotenoid, and finally converted the flower color from yellow to dark yellow. Comparative transcriptome analysis also showed that the 'carotenoid biosynthesis' pathway was significantly enriched, and genes involved in carotenoid degradation and ABA biosynthesis and metabolism were significantly down-regulated. Furthermore, we developed and validated the functional marker Br-dyp1-InDel for Br-dyp1. Overall, these results provide insight into the molecular basis of carotenoid-based flower coloration in B.rapa and reveal valuable information for marker-assisted selection (MAS) breeding in Chinese cabbage.